2015
DOI: 10.1007/s10722-015-0284-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural patterns and genetic diversity among oat (Avena) landraces assessed by microsatellite markers and morphological analysis

Abstract: As a counterweight to genetic erosion, landraces could become important germplasm resources for breeding. In the present study the genetic diversity of 62 Greek and Eastern European oat accessions (seven cultivars and 55 common and red oat landraces collected from 1904 to 1960) was studied using simple sequence repeats and 31 morphological descriptors. High levels of polymorphism were detected and 209 distinctive alleles were identified; on average 14.65 alleles per primer. Both, the principal component analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Since the oat panel presented a moderate population structure, parameters such as Q and K matrices and PCA covariates were implemented to correct models for stratification. Nevertheless, since A. sativa and A. byzantina have significant genetic/chromosomal differences, with byzantina type originated from the wild sterilis type and the sativa type originated from the wild fatua type ( Loskutov, 2008 ; Loskutov et al, 2011 ; Ladizinsky, 2012 ) and with genetic discrepancies reported by cytogenetics, FISH ( Sanz et al, 2010 ; Badaeva et al, 2011 ) and morphological/genetic markers ( Nikoloudakis et al, 2016 ), the identified markers might be correlated among taxa or “linked” to one of the two genotypic groups. To rule out this possibility, results were analyzed for each of the oat types separately.…”
Section: Discussionmentioning
confidence: 99%
“…Since the oat panel presented a moderate population structure, parameters such as Q and K matrices and PCA covariates were implemented to correct models for stratification. Nevertheless, since A. sativa and A. byzantina have significant genetic/chromosomal differences, with byzantina type originated from the wild sterilis type and the sativa type originated from the wild fatua type ( Loskutov, 2008 ; Loskutov et al, 2011 ; Ladizinsky, 2012 ) and with genetic discrepancies reported by cytogenetics, FISH ( Sanz et al, 2010 ; Badaeva et al, 2011 ) and morphological/genetic markers ( Nikoloudakis et al, 2016 ), the identified markers might be correlated among taxa or “linked” to one of the two genotypic groups. To rule out this possibility, results were analyzed for each of the oat types separately.…”
Section: Discussionmentioning
confidence: 99%
“…Even though morphological traits are generally employed in order to estimate genetic variation since their measurements are not laborious, still, diversity estimation based on morphology alone has limitations. Unfortunately, traits are heavily influenced by the environment, are limited in number and possibly unintentional selection for traits with agronomical value (Nikoloudakis et al, 2016).…”
Section: Identification Of Diverse and Desirable Accessionsmentioning
confidence: 99%
“…Based on morphological differences, one can pick and preserve genotypes for future use [18]. Unfortunately, morphological parameters are strongly influenced by the climate, which may positively or negatively affect a given plant and data for every locality around the globe is necessary for successful breeding of the given plant in a given locality [24].…”
Section: Discussionmentioning
confidence: 99%